2003
DOI: 10.1182/blood-2003-02-0495
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical in vivo evaluation of pseudotyped adeno-associated virus vectors for liver gene therapy

Abstract: We report the generation and use of pseudotyped adeno-associated viral (AAV) vectors for the liver-specific expression of human blood coagulation factor IX (hFIX). Therefore, an AAV-2 genome encoding the hfIX gene was cross-packaged into capsids of AAV types 1 to 6 using efficient, large-scale technology for particle production and purification. In immunocompetent mice, the resultant vector particles expressed high hFIX levels ranging from 36% (AAV-4) to more than 2000% of normal (AAV-1, -2, and -6), which wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
162
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(173 citation statements)
references
References 27 publications
9
162
2
Order By: Relevance
“…Although a high prevalence of NAbs against AAV2 is seen in humans, the incidence of NAbs to alternative types appears to be nonexistent or at lower titers (23,27). In vitro NAb assays, including those performed in this study, have demonstrated a lack of cross-reactivity between different types (22,23,26). The utilization of other types of AAV vectors to overcome AAV2 NAb activity has been performed in several animal models (27,55,64).…”
Section: Discussionmentioning
confidence: 99%
“…Although a high prevalence of NAbs against AAV2 is seen in humans, the incidence of NAbs to alternative types appears to be nonexistent or at lower titers (23,27). In vitro NAb assays, including those performed in this study, have demonstrated a lack of cross-reactivity between different types (22,23,26). The utilization of other types of AAV vectors to overcome AAV2 NAb activity has been performed in several animal models (27,55,64).…”
Section: Discussionmentioning
confidence: 99%
“…With identification of more AAV serotypes, the natural diversity of AAV capsids was utilized in terms of tissue-tropism and transduction efficiency by generation of pseudotyped vectors. 21 In comparison to AAV-2, AAV-6-pseudotyped vectors lead to higher myocardial transduction after intramyocardial injection and systemic administration. [22][23][24][25] Other AAV serotype vectors such as AAV-8 or -9 resulted in even higher cardiac transduction levels after intravenous injection in adult mice.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 These AAV serotypes share a common genome structure, but have varying abilities to infect different cell types and tissue based on their capsid protein recognition by cell surface receptors. The repertoire of rAAV vectors has also been greatly expanded by the development of technologies to pseudo-package rAAV genomes, [17][18][19][20] package AAV genomes with two different ITR serotypes, 21 generate mosaic rAAV particles with more than one capsid serotype, [22][23][24] retarget AAV by generating rAAV capsid modification [25][26][27][28][29] and generate rAAV with chemically modified capsids. 30 These technologies have greatly expanded the ability to tailor rAAV for specific applications in gene therapy.…”
Section: Introductionmentioning
confidence: 99%